ANALYSIS OF THE IMPACT OF MACROECONOMIC ENVIRONMENT ON THE ENTREPRENEURSHIP DEVELOPMENT - Njegomir, Vladimir; Radović, Milica M (Poslovna ekonomija, 2018)
In modern business conditions, entrepreneurship is a key factor in innovations, development of new products and services, employment creation of wealth and more efficient use of available resources. The role of entrepreneurship in the economy is extremely significant and has been proven in developed countries. Having in mind the enormous importance of entrepreneurship for economic development, we set the goal of the paper, which is the study of the impact of certain macroeconomic factors on the development of entrepreneurship in Serbia. In the paper, we first show importance of entrepreneurship in general and then on the characteristics of the entrepreneurship development in developed countries, developing countries and Serbia, and then we focus on key macroeconomic factors and their influence on the entrepreneurship development in Serbia. The underlying conclusion is that insufficient employment is a key factor for the entrepreneurship with the goal of self-employment, while favorable gross domestic product and income per capita are stimulating factors for entrepreneurship aimed at the development of innovations and economic and social progress.